Salter pelvic osteotomy in the treatment of Legg-Calve-Perthes disease : The medium term results - Bulut, Mehmet; Demirts, Abdullah; Ucar, Bekir Yavuz; Azboy, Ibrahim; Alemdar, Celil; Karakurt, Lokman (Acta Medica Belgica, 2014)
In this study, clinical and radiological results were evaluated in patients with Legg-Calve-Perthes disease treated with Salter pelvic osteotomy. Between 2004 and 2008, 16 patients underwent a Salter osteotomy as treatment for Legg-Calve-Perthes disease (15 male, 1 female; 10 right hip, 6 left hip). The mean age at the time of surgery was 8.1 +/- 1.4 (range : 6 to 10) years. Surgical indications were : age between 6-10 years at the onset of the disease; Herring classification type B, B/C, or C; and at least one risk sign. 6-8 year old patients were classified as group I and 9-10 year olds were classified as group II. We investigated the effects of age and Herring classification on radiological outcomes. The final radiographic evaluation according to the Stulberg classification showed nine hips (56.25%) classified as good (Stulberg I/II), five (31.25%) as fair (Stulberg III); and two (12.5%) as poor (Stulberg IV). In group I, 7 patients (70%) had good results, while only 2 (33.3%) in group II. The results in group I were statistically better than group II (p < 0.05). Based on the Herring lateral pillar type, of the 12 patients classified as B or B/C, at final follow-up, 8 (66.6%) had a good outcome (Stulberg HI), whereas in the four patients classified as type C, only one (25%) had a good outcome. The Salter pelvic osteotomy is an effective method of surgical treatment for Legg-Cave-Perthes in patients between 6-8 years of age.
Keywords: Legg-Calve-Perthes disease; Salter osteotomy; treatment outcome